2002
DOI: 10.1046/j.1463-1318.2002.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase expression of malignant epithelial cells correlates with Dukes' stage in colorectal cancer

Abstract: Pathological stage correlates with telomerase activity of the malignant cell population of the primary tumour in colorectal cancer. This suggests that telomerase activity increases during the progression of a cancer and may have implications for the design of anticancer (antitelomerase) agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…In agreement with several studies addressing telomerase activity in CRC (17,18,20,22), hTERT mRNA levels have been shown to gradually increase from normal mucosa to adenomas and carcinomas (14 -16). Nonetheless, hTERT mRNA has also been detected in telomerase-negative samples (23).…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with several studies addressing telomerase activity in CRC (17,18,20,22), hTERT mRNA levels have been shown to gradually increase from normal mucosa to adenomas and carcinomas (14 -16). Nonetheless, hTERT mRNA has also been detected in telomerase-negative samples (23).…”
Section: Discussionsupporting
confidence: 87%
“…Although the activity of this enzyme was recently shown to be upregulated by augmenting the gene transcription of hTERT by survivin, 34 contradictory results have been reported for the gastrointestinal tract. The majority of studies found upregulation of telomerase activity and mRNA expression in colorectal tumors, 17,[35][36][37] while others found increased activity only in late events during carcinogenesis but not in preneoplastic lesions. 38,39 In this context, contradictory results have been found in patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase activity is related to the Dukes' stage: patients at stage A and B showed a lower percentage of positivity than the ones at stages C or D [45,47,61,62,64,66] . Tumours localized in colon showed a higher percentage of positivity than tumours localized in the rectum [61,64] .…”
Section: Telomerase As a Colorectal Cancer Markermentioning
confidence: 99%
“…The overall survival and the disease-free survival of patients showing high telomerase activity was significantly worse than those for other patients. Telomerase activity was an independent prognosis-associated factor Ghori et al [66] , 2002 30/20 2 Lower rates of telomerase activity were detected in tumours at early stages Kawanishi-Tabata et al [69] , 2002 122 1 Telomerase activity detection is more frequent in colon than in rectal tumours at stage Ⅱ.…”
Section: Telomerase As a Colorectal Cancer Markermentioning
confidence: 99%